A COMMON DOLLAR FUNDS STATEMENT. - Beckert, Ralph F.; Thomas, Arthur L. (The Accounting Review, 1965)
Abstract One of the more troublesome hurdles facing the student in his first exposure to common dollar accounting is the reconciliation of changes in converted Retained Earnings. Even when he has satisfied himself of the way in which the converted net income figure is obtained, the gains and losses arising from holding monetary items during a period of price instability are apt to puzzle him. It is not only that their computation is initially hard to follow. Worse than that, these gains and losses are the one sort of item on the converted financial statements that does not correspond in a one-to-one fashion with an item already on the conventional, unconverted financial statements. Even when he has partially mastered the mechanical problem of calculating the related gains and losses, he will often be engaging in a sort of ritual rather than obtaining any real insight into what he is doing. In cases of this sort, it is sometimes helpful for the student to have an alternate way of looking at the thing that troubles him, a chance to see it emerge in another role.